The Strategy of Sustainable Waqf Development and Investment from the Perpective of Shariah - Sulaiman, Syahnaz; Hasan, Aznan (Academy of Islamic Studies, University of Malaya, 2017)
The initiative towards enhancing the role of waqf as the main driving force for socioeconomic development of the ummah has received tremendous support from the Muslim community globally. Much effort has been concerted by various waqf stakeholders to strengthen the role of the waqf institution as a socio-economic driving force which strives for the betterment of the global Muslim community. Special focus has been given to waqf development and investment agendas towards preserving waqf assets particularly in generating stable income in order to meet its objectives. Therefore, this study will explore the concept of sustainable waqf development and investment from the Islamic perspective and how strategic waqf development and investment approach may be implemented in light of the Shariah. The data used in this study was obtained from the literature review which was then analysed by using content and textual analysis technique. The findings further underline the strategy of sustainable waqf asset development and investment which should serve as a guide for the waqf administrators in the realization of sustainable development and investment in order to enhance the income of waqf assets for the benefit and welfare of the ummah.